Compositional and pressure controls on calcium and magnesium isotope fractionation in magmatic systems. (1st December 2020) - Chen, Chunfei; Huang, Jin-Xiang; Foley, Stephen F.; Wang, Zaicong; Moynier, Frédéric; Liu, Yongsheng; Dai, Wei; Li, Ming
Abstract: Stable isotope fractionation in magmatic systems depends on equilibrium isotope fractionation between different phases. However, current equilibrium stable isotope theory mostly assumes ideal crystal structures and simple chemical compositions, but it is unclear how the pressure and complex compositional variations in natural microscopic mineral structures affect inter-mineral stable isotope fractionation and thus control stable isotope fractionation in macroscopic magmatic systems. Here, we calculate the CaO and MgO bond lengths controlled by pressure and compositional variations of coexisting garnet (Grt) and clinopyroxene (Cpx) in the Roberts Victor eclogites from the Kaapvaal Craton and use these data as a proof of concept to interpret their inter-mineral Ca and Mg isotopic compositions (Δ 44/40 CaGrt-Cpx and Δ 26 MgGrt-Cpx ). Our results show that the CaO difference between Grt and Cpx (ΔCaOGrt-Cpx ) shows a significant increase with CaO content from 3.4 to 13.6 wt.% in Grt and with pressure from 2.9 to 6.9 GPa. ΔCaOGrt-Cpx has an excellent negative correlation with inter-mineral Ca isotope fractionation corrected for temperature effect (Δ 44/40 CaGrt-Cpx × T 2 /10 6 ), indicating that inter-mineral Ca isotope fractionation is controlled by pressure and compositional variations of the Grt through effects on the bond lengths. Inter-mineral Mg isotope fractionation corrected for temperature effect (Δ 26 MgGrt-Cpx × T 2 /10 6 ) in these eclogites shows a negative correlation with pressure but no obvious correlations with the mineral compositions, suggesting the dominant role of pressure effect in addition to temperature. The MgO bond length of Grt increases by about 0.02 Å with increasing CaO content in Grt of these eclogites, implying a mild compositional effect on inter-mineral Mg isotope fractionation. The results suggest that pressure and compositional variations in minerals control the equilibrium stable isotope fractionation between minerals. Utilizing the Ca isotope fractionation factor controlled by crystal chemistry of garnet, our modelling indicates that partial melting of eclogite in the mantle could not significantly fractionate Ca isotopes and, therefore, that low δ 44/40 Ca values in previously reported basalts cannot be attributed to the involvement of eclogite in their sources. This suggests that crystal chemistry exerts major controls on isotope fractionation in magmatic systems in addition to temperature.